Telomerase activity and telomere length in women with breast cancer or without malignancy: A systematic review and meta-analysis - Benites-Zapata, Vicente A. (2024)
Aim: We performed a systematic review and meta-analysis to assess whether telomerase activity and telomere length are associated with breast cancer. Methods: PubMed, Web of Science, Embase, LILACS, Scielo, Embase, and CNKI databases were searched to obtain relevant articles published through May 10, 2023, following PRISMA guidelines and a registered PROSPERO protocol (CRD42022335402). We included observational studies reporting telomerase activity or telomere length in patients with breast cancer compared with women with benign lesions or normal tissue (control women). The Newcastle–Ottawa Scale was used to evaluate the quality of studies. Data were expressed as odds ratios (OR) and 95 % confidence intervals (CI). Random effects and inverse variance methods were used to meta-analyze associations. The I2 test was used to assess heterogeneity. Results: The meta-analysis of telomerase shows significantly greater activity in patients with breast cancer than in those without malignancies (OR = 23.46, 95 % CI 14.07–39.11, p < 0.00001, I2 = 72 %). There were non-significant differences in relative telomere length (OR = 1.16, 95 % CI = 0.90–1.49, p = 0.26, I2 = 86 %) and leukocyte telomere length (OR = 2.32, 95 % CI = 0.89–6.08, p = 0.09, I2 = 98 %) between women with and without breast cancer. In subgroup analyses by world regions of studies, both telomerase activity and telomere length displayed the same trends as in their respective meta-analyses. In sensitivity analyses, variables showed their respective same trends. Conclusion: Telomerase activity is higher in patients with breast cancer than in women without malignancies. There were no significant differences in either relative telomere length or leukocyte telomere length in women with and without breast cancer. PROSPERO protocol CRD42022335402.